Correlation Between Duration of Using Silicone Oil Tamponade and Increased Intraocular Pressure - Farida, Nida; Nugraha, Ghina Fitria; Sari, Nurmila (The Avicenna Medical Journal, 2023)
Background: Silicone oil is an artificial liquid that functions as a tamponade agent in vitreoretinal surgery. One disadvantage of using silicone oil is that it needs advanced procedures for oil evacuation because it is not absorbed spontaneously by the retina. This evacuation is recommended as soon as the retina heals to prevent complications such as pupil block and glaucoma secondary to silicone oil (SO) emulsification and causing increased intraocular pressure (IOP).  The recommended time for SO evacuation is the first 3-6 months after surgery. The aims of this study is to determine the relationship between increased IOP and duration of use of tamponade SO.Methods: This study used a cross-sectional design by taking secondary data on retinal detachment history patients who underwent silicone oil evacuation at KMJA Hospital Jakarta from January 2019 to November 2021.Results: Respondents were 39 patients with an age range of 23-69 years and 71,8% were male. The average duration of use of SO is 9 months. In weeks 3-4 after the SO evacuation, data on the number of eyes with high IOP have obtained from as many as 9 eyes and 6 of them had used tamponade SO for more than 6 months with a p-value of 0.153.Conclusion: There was no significant association between the duration of SO tamponade use and increased IOP after SO evacuation.